Interaction of Dopamine with Zwitterionic DMPC and Anionic DMPS Multilamellar Vesicle Membranes - Sahu, Anand Kumar (Langmuir : the ACS journal of surfaces and colloids, 2021)
Dopamine (DA), a naturally occurring neurotransmitter, plays a crucial role in the function of the mammalian nervous system. DA-lipid-membrane interaction is inevitable during the neurotransmission process. In this report, we have studied the interaction of DA with anionic 1,2-dimyristoyl-sn-glycero-3-phospho-l-serine (DMPS), neutral (zwitterionic) 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), and synaptic membrane-mimicking mixed DMPC/DMPS (3:1 molar ratio) model multilamellar vesicle (MLV) membranes. Differential scanning calorimetry (DSC) studies suggest a strong specific interaction of DA with the anionic DMPS membrane, a weak interaction with the zwitterionic DMPC membrane, and a moderate interaction with the mixed DMPC/DMPS (3:1) membrane. The intrinsic fluorescence of DA was used as a new approach to gain a molecular-level understanding of DA-lipid-membrane interaction. Toward this end, a detailed photophysical study of DA, including its steady-state fluorescence anisotropy and fluorescence lifetime, was undertaken for the first time. The partition coefficient, location, and distribution of DA in the DMPS and DMPC model membranes were studied by employing intrinsic fluorescence. The effect of DA on the phase transition of the model membranes was also examined using the intrinsic fluorescence of DA. Zeta potential studies suggest a strong electrostatic interaction of DA with the anionic DMPS membrane and a nonspecific, relatively weak interaction of DA with the zwitterionic DMPC membrane. In addition, we observed cholesterol-induced DA expulsion from both DMPS and DMPC membranes. We believe that this work will provide a more in-depth understanding of DA-membrane interaction at a molecular level